2013
DOI: 10.1590/s0100-83582013000100019
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da chuva na eficiência de herbicidas aplicados em pós-emergência sobre corda-de-viola

Abstract: O objetivo deste trabalho foi avaliar a influência da chuva na eficiência de herbicidas aplicados em pós-emergência em plantas de Ipomoea grandifolia. As plantas de I. grandifolia foram cultivadas em vasos plásticos com capacidade de 2,5 L, em casa de vegetação, com uma planta por vaso. O delineamento experimental utilizado foi o inteiramente casualizado, com quatro repetições, com os tratamentos dispostos em um esquema fatorial 7x8 (sete tratamentos químicos e oito períodos para ocorrência de chuva após a apl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
2
0
2
Order By: Relevance
“…A different result was observed by SOUZA et al (2013), who, upon evaluating the influence of rains on the efficiency of herbicides sprayed on Ipomoea grandifolia plants, observed that all formulations based on glyphosate decreased control when there was a rain simulation, especially regarding treatments in which rainfalls occurred soon after spraying herbicides. MONQUERO; SILVA (2007) also reported a negative impact on the efficacy of glyphosate for the control of Euphorbia heterophylla and Ipomoea purpurea with the occurrence of rains after its application.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…A different result was observed by SOUZA et al (2013), who, upon evaluating the influence of rains on the efficiency of herbicides sprayed on Ipomoea grandifolia plants, observed that all formulations based on glyphosate decreased control when there was a rain simulation, especially regarding treatments in which rainfalls occurred soon after spraying herbicides. MONQUERO; SILVA (2007) also reported a negative impact on the efficacy of glyphosate for the control of Euphorbia heterophylla and Ipomoea purpurea with the occurrence of rains after its application.…”
Section: Resultsmentioning
confidence: 74%
“…Studies conducted to demonstrate the effects of rain on the efficacy of glyphosate after post-emergence application have shown that this herbicide decreases its control efficiency when rain occurs soon after its application (MARTINI et al, 2003;SOUZA et al, 2013;2014). However, control efficacy is also directly influenced by the various formulations available in the market and by the dose used (FENG et al, 2000;MONQUERO;SILVA, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Em relação a esse herbicida, outros trabalhos também demonstram a ineficiência de controle em doses de até 1.920 g e.a./ha. (Ramires et al, 2010;Souza et al, 2013;Agostineto et al, 2016). Esta ineficácia é ocasionada por mecanismos de tolerância da corda-de-viola como absorção e translocação diferencial.…”
Section: Resultsunclassified
“…Com relação ao glifosato, outros trabalhos também relataram a ineficiência de controle em doses de até 1920 g e.a. (RAMIRES et al, 2010;MARTINS;PEREIRA, 2013;AGOSTINETO et al, 2016). Esta ineficiência é causada por mecanismos de tolerância da corda-de-viola como absorção e translocação diferencial.…”
Section: Resultsunclassified